RESPON TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) TERHADAP PEMBERIAN BERBAGAI TAKARAN PUPUK KANDANG SAPI PO - Fatmawati, Nurlaila; Yanti, Alfi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The aim of this study was to determine the response of ground kale plants to various doses of PO cow manure and the best number of PO cow manure doses for growth and yield of ground kale plants. The research method used was a non-factorial Randomized Block Design (RBD) with five levels, namely without cow manure PO 0 tons/ha (control), cow manure concentration PO 10 tons/ha, cow manure concentration PO 20 tons/ha, concentration of cow manure PO 30 tons/ha and concentration of cow manure PO 40 tons/ha. Based on the results of the study, it was shown that the application of various doses of PO cow manure had no significant effect on the growth and yield of ground kale and the best number of PO cow manure doses was seen from the average observation parameter, namely at the concentration of PO cow manure of 20 tons/ha. Keywords: land kale, doses, cow manure PO